Luminescent supramolecular hydrogels from a tripeptide and nitrogen-doped carbon nanodots - Cringoli, Maria C.; Kralj, Slavko; Kurbasic, Marina; Urban, Massimo; Marchesan, Silvia (Beilstein Journal of Nanotechnology, 2017)
The combination of different components such as carbon nanostructures and organic gelators into composite nanostructured hydrogels is attracting wide interest for a variety of applications, including sensing and biomaterials. In particular, both supramolecular hydrogels that are formed from unprotected D,L-tripeptides bearing the Phe-Phe motif and nitrogen-doped carbon nanodots (NCNDs) are promising materials for biological use. In this work, they were combined to obtain luminescent, supramolecular hydrogels at physiological conditions. The self-assembly of a tripeptide upon application of a pH trigger was studied in the presence of NCNDs to evaluate effects at the supramolecular level. Luminescent hydrogels were obtained whereby NCND addition allowed the rheological properties to be fine-tuned and led to an overall more homogeneous system composed of thinner fibrils with narrower diameter distribution.
Keywords: carbon nanodots; composites; hydrogels; nanomaterials; peptide self-assembly

(untitled) - Baker, S. N.; Baker, G. A. (Angew. Chem., Int. Ed., 2010)

(untitled) - Miao, P.; Han, K.; Tang, Y.; Wang, B.; Lin, T.; Cheng, W. (Nanoscale, 2015)

(untitled) - Jiang, J.; He, Y.; Li, S.; Cui, H. (Chem. Commun., 2012)

(untitled) - Gude, V. (Beilstein J. Nanotechnol., 2014)

(untitled) - Marinovic, A.; Kiat, L. S.; Dunn, S.; Titirici, M.-M.; Briscoe, J. (ChemSusChem, 2017)

(untitled) - Arcudi, F.; Đorđević, L.; Prato, M. (Angew. Chem., Int. Ed., 2016)

(untitled) - Gogoi, N.; Barooah, M.; Majumdar, G.; Chowdhury, D. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Nguyen, C. T.; Tran, T. H.; Lu, X.; Kasi, R. M. (Polym. Chem., 2014)

(untitled) - Bhattacharya, S.; Nandi, S.; Jelinek, R. (RSC Adv., 2017)

(untitled) - Bhattacharya, S.; Sarkar, R.; Nandi, S.; Porgador, A.; Jelinek, R. (Anal. Chem., 2017)

(untitled) - Sun, W.; Wu, P. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Li, P.; Huang, L.; Lin, Y.; Shen, L.; Chen, Q.; Shi, W. (Nanotechnology, 2014)

(untitled) - Wang, H.; Yi, J.; Mukherjee, S.; Banerjee, P.; Zhou, S. (Nanoscale, 2014)

(untitled) - Baruah, U.; Konwar, A.; Chowdhury, D. (Nanoscale, 2016)

(untitled) - Sachdev, A.; Matai, I.; Gopinath, P. (Colloids Surf., B, 2016)

(untitled) - Hu, S.; Zhao, Q.; Dong, Y.; Yang, J.; Liu, J.; Chang, Q. (Langmuir, 2013)

(untitled) - Liu, C.; Li, F.; Yang, J.; Tian, F.; Sun, J. (J. Controlled Release, 2015)

(untitled) - Zhou, J.; Li, J.; Du, X.; Xu, B. (Biomaterials, 2017)

(untitled) - Cayuela, A.; Kennedy, S. R.; Soriano, M. L.; Jones, C. D.; Valcárcel, M.; Steed, J. W. (Chem. Sci., 2015)

(untitled) - Cayuela, A.; Soriano, M. L.; Kennedy, S. R.; Steed, J. W.; Valcárcel, M. (Talanta, 2016)

(untitled) - Ghosh, A.; Parasar, B.; Bhattacharyya, T.; Dash, J. (Chem. Commun., 2016)

(untitled) - Dasgupta, A.; Mondal, J. H.; Das, D. (RSC Adv., 2013)

(untitled) - Adams, D. J. (Macromol. Biosci., 2011)

(untitled) - Du, X.; Zhou, J.; Shi, J.; Xu, B. (Chem. Rev., 2015)

(untitled) - Marchesan, S.; Waddington, L.; Easton, C. D.; Winkler, D. A.; Goodall, L.; Forsythe, J.; Hartley, P. G. (Nanoscale, 2012)

(untitled) - Marchesan, S.; Qu, Y.; Waddington, L. J.; Easton, C. D.; Glattauer, V.; Lithgow, T. J.; McLean, K. M.; Forsythe, J. S.; Hartley, P. G. (Biomaterials, 2013)

(untitled) - Marchesan, S.; Waddington, L.; Easton, C. D.; Kushkaki, F.; McLean, K. M.; Forsythe, J. S.; Hartley, P. G. (Bionanosci., 2013)

(untitled) - Loo, Y.; Wong, Y.-C.; Cai, E. Z.; Ang, C.-H.; Raju, A.; Lakshmanan, A.; Koh, A. G.; Zhou, H. J.; Lim, T.-C.; Moochhala, S. M.; Hauser, C. A. E. (Biomaterials, 2014)

Non Invasive Diagnostic Techniques in Clinical Dermatology - Lademann, J.; Lange-Asschenfeldt, S.; Ulrich, M.; Darvin, M. E.; König, K.; Meinke, M. C.; Lange-Asschenfeldt, B. (Application of Laser Scanning Microscopy in Dermatology and Cutaneous Physiology, 2014)

(untitled) - Marchesan, S.; Vargiu, A. V.; Styan, K. E. (Molecules, 2015)

(untitled) - Yan, X.; Zhu, P.; Li, J. (Chem. Soc. Rev., 2010)

(untitled) - Melchionna, M.; Styan, K. E.; Marchesan, S. (Curr. Top. Med. Chem., 2016)

(untitled) - Wang, H.; Feng, Z.; Xu, B. (Adv. Drug Delivery Rev., 2017)

(untitled) - Iglesias, D.; Bosi, S.; Melchionna, M.; Da Ros, T.; Marchesan, S. (Curr. Top. Med. Chem., 2016)

(untitled) - Wu, C.; Biancalana, M.; Koide, S.; Shea, J.-E. (J. Mol. Biol., 2009)

(untitled) - Amdursky, N.; Erez, Y.; Huppert, D. (Acc. Chem. Res., 2012)

(untitled) - Biancalana, M.; Koide, S. (Biochim. Biophys. Acta, Proteins Proteomics, 2010)

(untitled) - Xue, C.; Lin, T. Y.; Chang, D.; Guo, Z. (R. Soc. Open Sci., 2017)

(untitled) - Cardoso, A. Z.; Alvarez Alvarez, A. E.; Cattoz, B. N.; Griffiths, P. C.; King, S. M.; Frith, W. J.; Adams, D. J. (Faraday Discuss., 2013)

(untitled) - Raeburn, J.; Zamith Cardoso, A.; Adams, D. J. (Chem. Soc. Rev., 2013)

(untitled) - Marchesan, S.; Styan, K. E.; Easton, C. D.; Waddington, L.; Vargiu, A. V. (J. Mater. Chem. B, 2015)

(untitled) - Kar, K.; Wang, Y.-H.; Brodsky, B. (Protein Sci., 2008)